La autodeterminación a debate / Juan José Solozabal (ed.) ; C. Aguado Renedo, J.M. Benegas, R. Blanco Valdés ... et al. - Solozábal Echavarría, Juan JoséAguado Renedo, César
Incluye referencias bibliográficas